A Functional Ecological Study of Municipal Towns in Nepal: A Factor Analysis Approach - Mandal, Umesh Kumar (Tribhuvan University Journal, 2010)
In the present study, an attempt has been made towards the application of factor analytical approach in the urban ecological study of Nepalese municipal towns. The 13 selected variables representing the major activities of urban population: agriculture, livestock, poultry and small scale non agriculture economic activities of 58 municipal towns have been taken into consideration in order to investigate the most important functional ecological dimensions of towns. Key words: Municipal towns; Functional ecology; Dimension rotated and unrotated; Common factor; correlation; loading; Eigen Value; communality; scree test; scatter plot Tribhuvan University Journal Vol. XXV, No. 1, 2005 Page:45-60 Uploaded date: 24, September, 2010